9+3x+(2x-2)=67

Simple and best practice solution for 9+3x+(2x-2)=67 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9+3x+(2x-2)=67 equation:



9+3x+(2x-2)=67
We move all terms to the left:
9+3x+(2x-2)-(67)=0
We add all the numbers together, and all the variables
3x+(2x-2)-58=0
We get rid of parentheses
3x+2x-2-58=0
We add all the numbers together, and all the variables
5x-60=0
We move all terms containing x to the left, all other terms to the right
5x=60
x=60/5
x=12

See similar equations:

| (x-12)+x=-5 | | 6-6x=6(x+7) | | 5x-8=123 | | 20-6x=50-26x | | -6(x-3)-4(x-2)=-4 | | 1/4(a+10)=10 | | n=13÷-1 | | 13+2x-14=x | | (3x-11)+x=49 | | 3x+4=7(x+2)+2 | | 10+x=5(x+2) | | 6+1x=33-2x | | m-12/4-4m-3/5=2 | | 9+3x+2x-2=67 | | 3x-7=9x-25 | | (x-4)(x-18)=x-14 | | 40-5x=-55 | | 12a+4a(2)+9=0 | | 8n-6(n+4)=-(-8+2n) | | -3=x-5/7 | | 70=28-14x | | 12a+4a*4a+9=0 | | 1/3x+1/4x=2x-17 | | 6y−3=6y+8 | | 42x+158=1166 | | 8x^2-48x=-135 | | 6y+5+5Y+7=15y-20 | | 129=3(8+5p) | | 2x/3=12/9 | | 4(v-2)=28 | | 17y=119 | | 3(4t-4)=10t1=7+2t |

Equations solver categories